Anger attacks and «anger disorders»: clinical relevance, problem of classification, comorbidity and therapy (review) - G. G. Simutkin (Обозрение психиатрии и медицинской психологии имени В.М. Бехтерева)
The review of literature data addresses the problem of diagnosis, classification, comorbidity, basic neurobiological mechanisms, as well as therapy of pathological manifestations of anger (“anger disorders”, anger attacks), considering into account the results of current epidemiological and clinical-biological studies.